2013 World Electric Vehicle Symposium and Exhibition (EVS27) 2013
DOI: 10.1109/evs.2013.6914957
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Class 8 hybrid-electric truck technologies using diesel, LNG, electricity, and hydrogen, as the fuel for various applications

Abstract: Class 8 trucks using various powertrains and alternative fuel options have been analysed to determine their fuel economy, greenhouse gas emissions, and economic attractiveness at the present time (2013) and in the future.This was done by modelling the vehicles and simulating their operation on day, short haul, and long haul driving cycles. The economic attractive was determined by calculating the differential vehicle cost of each powertrain option and the corresponding breakeven alternative fuel price needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 6 publications
3
30
0
Order By: Relevance
“…The determined battery capacities are significantly higher than the values of 270 kWh and 400 kWh assumed in comparable studies [12,13] due to the specified driving period and routes. The determined capacity values are used for the simulation of the transport scenarios specified in the next section and the integration of the traction battery into the truck is analyzed in Section 3.2.…”
Section: Definition Of Transportation Scenariosmentioning
confidence: 57%
“…The determined battery capacities are significantly higher than the values of 270 kWh and 400 kWh assumed in comparable studies [12,13] due to the specified driving period and routes. The determined capacity values are used for the simulation of the transport scenarios specified in the next section and the integration of the traction battery into the truck is analyzed in Section 3.2.…”
Section: Definition Of Transportation Scenariosmentioning
confidence: 57%
“…The primary motivation behind this was to compare the fuel economy improvements that can be achieved by the hybridization of a diesel-based powertrain and a gas-based powertrain. It is assumed that such a powertrain modification could be relevant for those HD vehicles, whose operating schedules include a considerable share of city and suburban haulage since the major effect of HD powertrain hybridization is expected in conditions allowing for intensive use of regenerative braking, which is the most efficient tool for increasing the fuel economy of vehicles with large masses [10].The published studies (see, for example, [11][12][13][14]) have demonstrated that hybrid HD vehicles having a gross mass ranging 16 to 36 tons possess a significant fuel-saving potential in city driving conditions, especially in the case of full hybridization, which offers up to 35% fuel consumption reduction. The mild degree of hybridization is able to provide moderate fuel savings of about 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The fuel economy of powertrains, which use different kinds of fuels, cannot be compared directly. One can evaluate the energy content of the consumed fuel [15], or the CO 2 emissions of compared vehicles [12,15], or the economic aspect, i.e., fuel price [12,15,16]. This work employed another approach stemming from the goal of hybridization, namely to reduce the fuel consumption relative to the baseline powertrain.…”
Section: Introductionmentioning
confidence: 99%
“…To reverse this trend, a variety of technologies have emerged in recent years, primarily driven by the development in the passenger vehicle sector (Zhao, Burke, & Zhu, ). Besides the total or partial electrification of the drivetrain using hybrid electric vehicles (HEV), battery electric vehicles (BEVs), or fuel cells electric vehicles (FCEV), substituting diesel with liquefied natural gas (LNG) promises a reduction in GHG emissions.…”
Section: Introductionmentioning
confidence: 99%